2000
DOI: 10.1002/(sici)1096-8652(200005)64:1<76::aid-ajh15>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma presenting high fever and high serum levels of lactic dehydrogenase, CRP, and interleukin-6

Abstract: Two myeloma patients presented high fever with no signs or data indicating infection at diagnosis or relapse. Both patients had plasmablastic myeloma, and serum levels of lactic dehydrogenase (LDH) and CRP were extremely high. Plasmablastic morphology, high LDH, and CRP were recognized as poor prognostic factors, indicating a fulminant phase of multiple myeloma. Interleukin-6 (IL-6) was only high in measured cytokines. We proposed that IL-6 caused high fever and induced the fulminant phase in these 2 cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
(2 reference statements)
1
6
0
Order By: Relevance
“…Barlogie et al reported that high levels of serum LDH associated with high-grade lymphoma-like myeloma (Barlogie et al, 1989). Different studies reported high serum levels of LDH, CRP, IL-6, and the high fever in the course of multiple myeloma have been indicated poor prognostic rate with terminal stage (Barlogie et al, 1989;Murakami et al, 2000). Direct myeloma cell infiltration and amyloid deposit in lungs tissues associates with terminal stages of multiple myeloma (Suchman et al, 1981;Meijer et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Barlogie et al reported that high levels of serum LDH associated with high-grade lymphoma-like myeloma (Barlogie et al, 1989). Different studies reported high serum levels of LDH, CRP, IL-6, and the high fever in the course of multiple myeloma have been indicated poor prognostic rate with terminal stage (Barlogie et al, 1989;Murakami et al, 2000). Direct myeloma cell infiltration and amyloid deposit in lungs tissues associates with terminal stages of multiple myeloma (Suchman et al, 1981;Meijer et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…APPs also have potential as early and reliable signs of inflammation associated with other disease processes, including malignancies 3 . Recently, CRP has been evaluated in both humans and dogs with cancer, such as lymphoma, multiple myeloma, pancreatic cancer, squamous cell carcinoma, and colorectal cancer 4–14 …”
Section: Serum Haptoglobin and C‐reactive Protein Concentrations In mentioning
confidence: 99%
“…[12][13][14][15] In human medicine, serum CRP concentration has been used as a prognostic factor for patients with lymphoid Serum C-reactive protein concentrations in dogs with multicentric lymphoma undergoing chemotherapy neoplasia and as a marker for cancer remission and relapse. [16][17][18][19][20][21][22] However, it is not known whether serum CRP concentration is altered in dogs with lymphoma or whether the concentration will change in dogs undergoing chemotherapy. In addition, although serum concentrations of some acute-phase proteins (eg, haptoglobin) have been shown to increase after administration of corticosteroids, 23,24 it is not known whether this is true for CRP concentration in dogs.…”
mentioning
confidence: 99%